Spatiotemporal analysis of Seismicity Parameters (a- and b-values) for Earthquake Disaster Mitigation: A case study of the 2018 Lombok Earthquake, Indonesia - Sarjan, Achmad Fajar Narotama (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study analyzes the seismicity parameters of Lombok Island using ZMAP 7.1 to better understand the region’s earthquake characteristics. The results indicate a high level of seismic activity, with an a-value of 10.257 and an annual a-value of 8.743, corresponding to an average of approximately nine earthquakes per year. The calculated b-value of 1.58 ± 0.07 also reflects high seismicity, suggesting that rocks in the study area have a limited capacity to withstand stress and store energy, thereby favoring the occurrence of low-magnitude events. Conversely, zones with lower b-values are relatively stronger and capable of generating higher-magnitude earthquakes. The predominance of moderate to high b-values across Lombok Island indicates that much of the accumulated energy was released during the 2018 earthquake sequence associated with the Flores back-arc thrust.